Methodological aspects of the implementation of Printmaking in Pre-school, Primary and Secondary education - Vojvodić, Milica; Sredanović, Jelena (Arte, Individuo y Sociedad, 2020)
Printmaking, with its technical complexity, has often been neglected in educational praxis, even though it is a discipline which contributes significantly in the developing of children`s creativity. In this work, alternative, non-toxic printmaking techniques have been presented and they are adapted to school conditions and age abilities of children. Art teacher needs to be adequately trained so he could make this art medium closer to children. Initial education teachers get at faculties has an important role in empowering their vocational competences, but a significant place in that process may also take specialized programs of professional training which leads to achieving specific knowledge and skills in printmaking. With suitable education and implementation of modern methodological aspects, teachers have an opportunity to introduce children to values of printmaking and have affirmative effect on the development of children`s art expression.